A new approach to kidney wait‐list management in the kidney allocation system era: Pilot implementation and evaluation. Issue 11 (15th October 2018) - Cheng, Xingxing S.; Busque, Stephan; Lee, Jenny; Discipulo, Kevin; Hartley, Christine; Tulu, Zeynep; Scandling, John D.; Tan, Jane C.
Abstract: Kidney transplant wait‐list management is becoming increasingly complex. We introduced a novel wait‐list management strategy at our center, the Transplant Readiness Assessment Clinic (TRAC), whereby patients whose Kidney Allocation Scores surpass a threshold are actively managed. From January 1, 2016 through June 30, 2017, we evaluated 195 patients through TRAC. Compared to pre‐TRAC systems at our institution, TRAC resulted in a higher proportion of activation at 18 months (38% vs 22%‐26%, P < 0.0001), despite being enriched in patients with long dialysis duration. TRAC also resulted in a higher proportion of wait‐list removal (15% vs 8%‐9%, P < 0.05) although combined wait‐list removal and death on wait‐list did not differ (18% vs 16%‐17%). Median time to activation was 356 days from TRAC evaluation. Of the transplant barriers, need for cardiovascular studies was the most common (31%), followed by other medical issues (23%), poor functional status (13%), and psychosocial issues (10%). By concentrating center resources on patients most likely to be transplanted after activation and performing active patient management close to the time of transplant, TRAC has the potential to significantly enhance kidney transplant success in regions with long wait‐times.